CAPITAL STRUCTURE OPTIMISATION AND WACC MINIMISATION IN REGIONAL INDUSTRIAL ENTERPRISES: AN ECONOMETRIC APPROACH (American Journal of Research in Humanities and Social Sciences, 2026)
This article examines the optimal capital structure of regional industrial enterprises through the lens of the trade-off theory and the Weighted Average Cost of Capital (WACC) minimisation framework. We develop an econometric model integrating the CAPM-based equity cost estimation with a System GMM dynamic panel specification to identify the causal relationship between leverage and enterprise value creation. Using panel data from 148 industrial enterprises in Kashkadarya Region, Uzbekistan (2018–2023), we demonstrate that the optimal debt-to-equity ratio — the "turning point" in the U-shaped WACC function — lies within the range of 35–45%, beyond which marginal bankruptcy costs outweigh tax shield benefits. The findings provide an evidence-based framework for capital allocation decisions in transitional industrial economies.